2016
DOI: 10.1080/0309877x.2016.1159293
|View full text |Cite
|
Sign up to set email alerts
|

Motivation of Emirati males and females to study at higher education in the United Arab Emirates

Abstract: This article reports on a study into the motivation of young Emirati undergraduate students for studying in a higher education institution in the United Arab Emirates. The participants were male and female undergraduate students in their first or second year of studying. The aim of the study was to examine their motivation using a framework that recognized the unique sociocultural context of the UAE. Data were analysed according to an adapted framework encompassing both Self-Determination Theory and Personal I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previous studies (Al-Fattal, 2010;Al Hallak, Ayoubi, Moscardini anda Loutfi, 2019;Tin, Ismail, Othman and Sulaiman, 2012;Engin and McKeown, 2017;Henry, 2012;Hossler, Braxton, and Coopersmith, 1989;Hoyt and Brown, 2003;Kim and Gasman, 2011;Kusumawati, 2013;Maniu and Maniu, 2014;Migin, Falahat, Yajid and Khatibi, 2015;Obermeit, 2012;Shah, Sid Nair and Bennett, 2013;Pritchard et al 2018, Pawar et al 2019Singh, 2019;Busher and James, 2019;Nghia, 2019) have investigated the process of students' university choice thoroughly and some have identified a number of factors that affect the students' university choice decision. However, most of these studies have been conducted in the developed countries such as the United States of America, Britain, Australia and Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Al-Fattal, 2010;Al Hallak, Ayoubi, Moscardini anda Loutfi, 2019;Tin, Ismail, Othman and Sulaiman, 2012;Engin and McKeown, 2017;Henry, 2012;Hossler, Braxton, and Coopersmith, 1989;Hoyt and Brown, 2003;Kim and Gasman, 2011;Kusumawati, 2013;Maniu and Maniu, 2014;Migin, Falahat, Yajid and Khatibi, 2015;Obermeit, 2012;Shah, Sid Nair and Bennett, 2013;Pritchard et al 2018, Pawar et al 2019Singh, 2019;Busher and James, 2019;Nghia, 2019) have investigated the process of students' university choice thoroughly and some have identified a number of factors that affect the students' university choice decision. However, most of these studies have been conducted in the developed countries such as the United States of America, Britain, Australia and Germany.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with Hewlett and Rashid's (2010) observations that the Emirate female students are highly motivated to have top positions in their jobs. Similarly, Engin and McKeown (2016) found that female Emirati students in particular see university education as a way to fulfill their dreams of an ideal job. Data from these studies suggests that motivation is a central, perhaps the central, factor encouraging female students to acquire and use more LLL skills in comparison to male students.…”
Section: Discussionmentioning
confidence: 99%
“…Findlow also argued that there was an incongruity between society's desire to educate women and the realities of employment opportunities for them after completing university. Three years later, Engin and McKeown (2016) raised similar concerns: "Are female students able to participate in the workforce as fully as they talk about?" (p. 13).…”
Section: Emirati Women In Higher Education In the Uaementioning
confidence: 99%